In utero Exposure to Valproic-Acid Alters Circadian Organisation and Clock-Gene Expression: Implications for Autism Spectrum Disorders - Ferraro, Sarah; de Zavalia, Nuria; Belforte, Nicolas; Amir, Shimon (Frontiers in Behavioral Neuroscience, 2021)
Autism Spectrum Disorder (ASD) is a pervasive neurodevelopmental disorder characterized by restrictive patterns of behaviour and alterations in social interaction and communication. Up to 80% of children with ASD exhibit sleep-wake cycle disturbances, emphasizing the pressing need for novel approaches in the treatment of ASD-associated comorbidities. While sleep disturbances have been identified in ASD individuals, little has been done to assess the contribution of the circadian system to these findings. The objective of this study is to characterize circadian behaviour and clock-gene expression in a valproic acid (VPA)-induced animal model of autism to highlight perturbations potentially contributing to these disturbances. Male and female VPA-exposed offspring underwent circadian challenges, including baseline light-dark cycles, constant dark/light and light pulse protocols. Baseline analysis showed that VPA-exposed males, but not females, had a greater distribution of wheel-running behaviour across light-dark phases and a later activity offset (p < 0.0001), while controls showed greater activity confinement to the dark phase (p = 0.0256). Constant light analysis indicated an attenuated masking response and an increase in the number of days to reach arrhythmicity (p < 0.0001). A 1-hour light pulse (150 lux) at CT 15 after six days of constant dark showed that both sexes exposed to VPA exhibited a lesser phase-shift when compared to controls (p = 0.0043). Immunohistochemical and western-blot assays reveal no alterations in retinal organization or function. However, immunohistochemical assay of the SCN revealed altered expression of BMAL1 expression in VPA-exposed males (p = 0.0016), and in females (p = 0.0053). These findings suggest alterations within the core clockwork of the SCN and reduced photic-entrainment capacity, independent of retinal dysfunction. The results of this study shed light on the nature of circadian dysregulation in VPA-exposed animals and highlights the urgent need for novel perspectives in the treatment of ASD-associated comorbidities.